SWEET transporters in plants and their significance in Sugarcane - Abdul Ameer, Afseena; Perumal Thirugnanasambandam, Prathima P.T; V. P, Rabisha; M Ram Vannish; Basheer, Swaliha (Journal of Sugarcane Research, 2024)
Sugars will eventually be exported transporters (SWEETs) are recently discovered bidirectional uniporters that play a significant role in various physiological and developmental processes in plants including pollen nutrition, nectar secretion, seed filling, and combating abiotic stresses. SWEETs are also responsible for pathogen susceptibility in many plants. Although the structure and evolutionary relationships of various SWEETs have been revealed, insights into the regulatory mechanisms of SWEET expression remain the basis for developing improved varieties of crops. This review discusses many relevant updates on SWEET research in plants. We also examine how transcriptional activator-like effector nucleases (TALENs) and CRISPR/Cas9 genome editing tools derive pathogen-resistant plants for crop improvement.